Cloning, expression and characterization of antifungal protein gene (Endo-β-1,3-1,4-glucanase) from Bacillus sp. strain 289 against sheath blight disease pathogen, Rhizoctonia solani - Bunawan, Siti Noraini (2015)
Rhizoctonia solani is a destructive fungal that caused sheath blight disease in rice. Infection by R. solani has caused a serious threat and yield loss in rice industry worldwide. The management of sheath blight disease is mainly through chemical control but it is not considered as long term solution due to environmental and health concerns. Therefore, as an alternative option by using biological control agent, this study was done with the objective to isolate antagonist bacteria against R. solani. This research is also aimed to isolate,express and characterize potential antifungal protein, endo-β-1,3-1,4-glucanase (βglu) from the best isolated antagonist bacteria using protein recombinant technology. A total of 390 pure culture bacteria were isolated from 60 soil samples collected from six different paddy field locations in Seberang Perai, Penang. Subsequently, the isolates were screened for growth inhibition activity on R. solani. There were 13 isolates exhibited antifungal activity with the highest inhibition zone was 22 ± 0.58 mm. Isolate with the highest inhibition zone was proceed for bacterial genus identification. Based on the biochemical profile identification results, 16S rRNA BLAST sequence analysis and phylogenetically related microorganism, the isolate SP 289 is in the genus of Bacillus and therefore is assigned tentatively as Bacillus sp. 289. Isolation of the βglu showed an open reading frame of 720 bp in length which codes for 239 amino with molecular weight of 26.7 kDa. The gene was then cloned into pRSET A as expression vector and expressed in E. coli BL21. IPTG was used to induce the expression of the T7 RNA polymerase. The optimum time for the growth of E. coli BL21 to express the highest production of βglu was at one hour after induction with the IPTG. The recombinant βglu was purified through affinity column using Ni-NTA resin. Characterization of the recombinant βglu enzyme showed optimum activity at 50 ⁰C and optimum pH at pH 6. Enzyme activity was retained at almost 100 % after being preincubated for 30 minutes between 30 ⁰C to 50 ⁰C while pH stability profile showed the activity remained above 68 % at pH ranging from pH 5 to pH 10 upon treatment at 50 ⁰C for 30 minutes in various buffers. Initial rates of βglu against lichenan concentration exhibited a Km of 7.29 ± 2.57 mg/mL and a Vmax of 68.16 ± 10.42 U/mg. Bioassay test against the sheath blight pathogen was also done. The recombinant βglu was found to inhibit the growth of R. solani mycelium and the inhibition was increased with the increased of enzyme concentration. With this finding, βglu enzyme has potential as biological control for R. solani while the gene can be use in the development of transgenic rice resistant to sheath blight disease. This is the first report regarding the antifungal activity of endo-β-1,3-1,4-glucanase enzyme isolated from bacteria especially in inhibiting the growth of R. solani.